The varied sources of faculae-forming brines in Ceres’ Occator crater emplaced via hydrothermal brine effusion - J. E. C. Scully (Nature Portfolio, 2020)
The second extended phase of the Dawn mission provided high resolution observations of Occator crater of the dwarf planet Ceres. Here, the authors show that the central faculae were sourced in an impact-induced melt chamber, with a contribution from the deep brine reservoir, while the Vinalia Faculae were sourced by the deep brine reservoir alone.